Successful Treatment of Concurrent Cholangiohydatidosis with Obstructive Jaundice and Hepatothoracic Transit in a Pediatric Patient - Tepeneu, Narcis Flavius; Popoiu, Călin Marius; Iacob, Emil Radu; Cerbu, Simona; Belei, Oana; Heredea, Rodica (European Journal of Pediatric Surgery Reports, 2025)
Concurrent rupture of hepatic hydatid cysts into the biliary tree and into the pleural cavity is a very rare complication in echinococcosis and can pose diagnostic and treatment challenges. We present the case of a 15-year-old female patient with recurrent abdominal pain, chest pain, fever, vomiting, jaundice, and cholangitis. Ultrasound, X-rays, computed tomography of the abdomen and thorax and cholangio-magnetic resonance imaging revealed a hepatic hydatid cyst with rupture into the main biliary duct causing obstruction, gallbladder microlithiasis, rupture of the right hemidiaphragm, and pleural hydatidosis. Echinococcus serology tests were positive. Endoscopic retrograde cholangiopancreatography (ERCP) could not resolve the obstructive jaundice. A laparotomy with choledochotomy, removal of hydatid structures, choledochal drainage with Kehr tube, cholecystectomy, Lagrot partial pericystectomy, partial pleural resection, suturing of the diaphragm, and triple drainage (right pleural cavity, cystic cavity, and Douglas pouch) was performed. Perioperative albendazole and antibiotic therapy was administered. The patient had an uneventful postoperative course. Follow-up at 1, 6, 12, and 24 months showed a favorable evolution without relapse of the hydatidosis. The very rare complications of cholangiohydatidosis and concomitant hepatothoracic transit lead to a severe condition, which needs adequate surgical treatment. Clinical presentation and laboratory findings are not specific and may simulate an obstructive jaundice and acute cholangitis of other etiology. ERCP with endoscopic papillotomy offers the advantage of a minimally invasive surgery, but it does not allow a definitive treatment of the whole problem and may be useful as a bridge procedure to drain the bile duct while awaiting definitive surgery.
Keywords: cholangiohydatidosis; hepatothoracic transit; echinococcus serology; ERCP